LOGISTICS MANAGEMENT OF INTERNATIONAL PASSENGER TRANSPORTATION ROUTES PARAMETERS FORMING - Khalipova, N. V.; KuzmenkoА. I.; CherchataА О.; Havryliuk, V. V. (Systems and Technologies, 2025)
The article addresses the urgent issue of forming effective transport and logistics support in organizing international passenger transportation. An economic and mathematical model of logistics management in the development of international tourist routes between Ukraine and Europe is proposed. The model is associated with the traveling salesman problem, where all designated points must be visited exactly once in a closed loop with minimum total cost, returning to the starting point. The purpose of the study is to develop efficient processes for international bus transportation in the Ukraine–Europe direction.To achieve this goal, the following tasks were accomplished: the main trends in the development of international passenger transportation in Ukraine were analyzed; an algorithm for forming a transport and logistics scheme for international transportation in the Ukraine–Europe direction was developed; a mathematical model of logistics management was proposed; and economic and mathematical modeling was conducted to determine the optimal tourist route through cities in Poland and analyze the results.Based on the analysis of current trends in international bus transportation and the factors influencing increased demand, an algorithm for building a transport and logistics scheme in the Ukraine–Europe direction was developed. This scheme takes into account both preliminary and operational forecasts of passenger flows, as well as the results of modeling queueing systems during formal border-crossing procedures for buses (via green and red corridors), and the real conditions with queues and service channels at international checkpoints.The main focus is on choosing the most efficient tourist travel routes. This issue is particularly relevant today due to the rapid development of international relations and the global tourism industry. Factors influencing the selection of destinations, time spent in cities, and the impact of a location’s attractiveness on the optimal duration of cultural and historical site visits were analyzed.Using the example of seven of the most popular cities in Poland, modeling was carried out and the optimal route was determined. As a result, the route Lviv–Krakow–Oswiecim–Wroclaw–Poznan–Gdansk–Warsaw–Lviv was found to have the shortest total length by road – 1788 km.The proposed approach should contribute to an increase in the number of trips along popular routes, more efficient use of the bus fleet of transport enterprises, and improved convenience and service quality for passengers (in terms of time, transfers, etc.). Overall, it will help increase the profitability of transport companies and better meet the needs of transport service consumers.